2021
DOI: 10.3389/fpls.2021.660430
|View full text |Cite
|
Sign up to set email alerts
|

New Players in the Interaction Between Beetle Polygalacturonases and Plant Polygalacturonase-Inhibiting Proteins: Insights From Proteomics and Gene Expression Analyses

Abstract: Plants possess various defense strategies to counter attacks from microorganisms or herbivores. For example, plants reduce the cell-wall-macerating activity of pathogen- or insect-derived polygalacturonases (PGs) by expressing PG-inhibiting proteins (PGIPs). PGs and PGIPs belong to multi-gene families believed to have been shaped by an evolutionary arms race. The mustard leaf beetle Phaedon cochleariae expresses both active PGs and catalytically inactive PG pseudoenzymes. Previous studies demonstrated that (i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…PG has been widely described in fungi, bacteria, nematodes, and plants [ 102 ]. In insects, PGs have been reported in many orders with piercing-sucking and chewing mouthparts, beetles (Coleoptera, mainly of the Phytophaga clade) are included and notably common in mirid bugs (Hemiptera) [ 103 105 ]. Mirid PGs can cause much larger lesions than superficial mechanical damage or feeding by other sap-sucking insects [ 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…PG has been widely described in fungi, bacteria, nematodes, and plants [ 102 ]. In insects, PGs have been reported in many orders with piercing-sucking and chewing mouthparts, beetles (Coleoptera, mainly of the Phytophaga clade) are included and notably common in mirid bugs (Hemiptera) [ 103 105 ]. Mirid PGs can cause much larger lesions than superficial mechanical damage or feeding by other sap-sucking insects [ 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, PGIPs from V. radiata, VrPGIP1, and VrPGIP2 ( Kaewwongwal et al, 2017 ; Zhang et al, 2021 ) and Brassica rapa ssp. pekinensis BrPGIPs ( Haeger et al, 2021 ) have shown to inhibit insects and P. sativum PsPGIP inhibited nematodes ( Veronico et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogens secret various cell wall-degrading enzymes (CWDEs), such as polygalacturonases, to depolymerize cell wall polysaccharides and subsequently compromise cell wall integrity (1). Polygalacturonases are produced by various pathogens, and their involvement in pathogenesis has been wellestablished (2)(3)(4)(5)(6). Pathogenic and certain plant-derived polygalacturonases belong to endo-glycoside hydrolase 28 family (endopolygalacturonases).…”
mentioning
confidence: 99%